The use of crotalaria as possible indirect agent to control Aedes aegypti L. (Diptera: Culicidae) - Schneider, Barbara Clara (2020)
Aedes aegypti L. (Diptera: Culicidae) is a vector of arboviruses associated with dengue, chikungunya, zika and yellow fever. Based on empirical knowledge, plants belonging to genus Crotalaria (Fabaceae) attract dragonflies, which are the main natural predator to A. aegypti and help controlling populations of this mosquito. The aim of the present study is to investigate (i) whether Crotalaria is a food source for A. aegypti and (ii) whether Crotalaria attracts predators to this mosquito, mainly dragonflies. The study was carried out from January to March 2018 in two Crotalaria spectabilis Roth (Fabaceae) cultivation fields, which covered 100 m2 (each) in Missal County, Paraná State, Brazil. Samples of all arthropods foraging on C. spectabilis were collected. Observations in situ were carried out to investigate whether A. aegypti individuals visit C. spectabilis flowers. In total, 14,967 arthropods were recorded foraging on C. spectabilis (288 in cultivation field 1 and 14,679 in cultivation field 2). Dragonflies and damselflies were recorded foraging on C. spectabilis crops, but no A. aegypti individual was recorded in active collections and observations in situ. These results indicate that C. spectabilis works as food source and/or place used by several arthropods to find preys. The incidence of dragonflies and damselflies flying in C. spectabilis monocultures indicates that these plants attract dragonflies, as well as that Crotalaria can help indirectly controlling A. aegypti populations.